Delayed post-traumatic diaphragmatic rupture complicated by total hepato-thorax: A case report - Kastanakis, Miltiades (Elsevier, 2013)
INTRODUCTION: Intra-thoracic herniation of abdominal organs following diaphragmatic rupture represents an unusual clinical occurrence that poses great diagnostic difficulty. PRESENTATION OF CASE: We report a rare case of delayed total hepatothorax caused by a right sided post-traumatic diaphragmatic rupture in a 67 year old male. Reduction of the liver in the abdominal cavity and repair of the diaphragm was feasible via a thoraco-abdominal approach. Postoperative chest radiography showed normal position of the right diaphragmatic border. DISCUSSION: Characteristics of right diaphragmatic rupture and subsequent complications are reviewed with the aim to reinforce physicians’ awareness of this uncommon clinical condition in order to establish a timely diagnosis and reduce the mortality related burden. CONCLUSION: Surgeons should consider this entity in the differential diagnosis of injured patients experiencing sudden respiratory distress during hospitalization as well as days or months after discharge.